The Study of the Morphologies of Nuclear Grade Zirconium Sponge - M Asadi Asadabad; M Zolfaghari Ataabadi; S. A. H Emami (مجله علوم و فنون هسته‌ای, 2016)
The morphology of zirconium sponge formed during the Kroll process could be more important due to its effect on composition, amount of impurities and efficiency of the sponge durability in the subsequent intermediate processes. In this research, various samples were prepared from different stages of the process and different zones of the products. In order to evaluate the products, scanning electron microscopy (SEM) and X-Ray diffraction (XRD) techniques were used. XRD analysis of the zirconium sponge showed that the amounts of magnesium chloride and retained magnesium in sponge texture were at a high level after the reduction process and were distributed non-uniformly in various parts of the sponge in which the amounts of impurities in the center was higher than the other parts. Also, examination by the scanning electron microscopy showed that the prime morphology of the zirconium sponge particles is irregular. Chemical analysis indicated that the excretion of magnesium impurities from the sponge will be more desirable in the distillation process, when the sponge morphology is in needle–like shape. If there is not enough time for the distillation process, the amount of magnesium and chloride impurities in the center of zirconium sponge will be higher in comparison to the other areas. So, for maximum elimination of such impurities in the distillation process, sufficient time duration has to be considered. Despite the fact that the distillation process is time-consuming and expensive, the impurity elimination compared to the proceses of chemical purifying is more favourable